Taxonomy and distribution of a common arboreal lizard, Bronchocela jubata Duméril & Bibron, 1837 (Reptilia: Agamidae), with designation of its lectotype from Java, Indonesia - Amarasinghe, A.a. Thasun; Ineich, Ivan; Riyanto, Awal; Hallermann, Jakob; Andayani, Noviar; Abinawanto, A.; Supriatna, Jatna (Zootaxa, 2022)
Bronchocela jubata Duméril and Bibron, 1837 is one of the commonest species of the genus, known mostly from Java Island and southern parts of Sumatra. It is rare in Bali and Borneo. The juveniles are often confused with its morphologically similar congener, B. cristatella, which occurs widely throughout the Indonesian Archipelago and Peninsular Malaysia. We examined the morphology of B. jubata based on museum specimens including its two available syntypes, and redescribed the species based on the lectotype designated herein. We highlight the characters of B. jubata with a morphometric comparison to its sympatric congener B. cristatella from Java Island, Indonesia. Based on the current distribution pattern and the apparent threats, we update the conservation status of B. jubata using IUCN Red List Criteria, and propose that it be considered as a species of Least Concern (LC), endemic to the Greater Sundaic Islands.